EPONYMOUS CITATIONS TO HOMI JEHANGIR BHABHA - Swarna, T.; Kalyane, V. L.; Prakasan, E. R.; Kumar, Vijai (Malaysian Journal of Library and Information Science, 2004)
The epoch-making research by H. J. Bhabha has gained eponymous status synonymous with his name and international fame. Out of the 427 eponymous bibliographic records for H. J. Bhabha retrieved from the Science Citation Index (1982-2002), majority of the records were for: bhabha scattering (290), angle bhabha scattering (42), small angle bhabha scattering (21), radiative bhabha scattering (17), large-angle bhabha scattering (16), resonant bhabha scattering (12), and low-angle bhabha scattering process (10). Percentage scattering of the eponyms in various bibliographic zones were: KeyWords Plus (47.16%), Abstract (26.79%), Title (22.75%), and Author keywords (3.3%). Based on terminological similarities of the eponyms, 19 clusters were formed. The keyword ‘photon corrections’ occurred in eight clusters whereas ‘bhabha scattering’, ‘cross section(s)’, ‘gauge-theories’, ‘high-energies’, and ‘multiple bremsstrahlung’ each one was common to seven clusters. Content analysis based on the presence of keywords among the clusters using number of common keywords was attempted as a pilot study and depicted as a dendrogram. Non-Indexed Eponymal Citedness (NIEC) is a significant phenomenon that should not be neglected while documenting the citations to an individual scientist.